Promoting healthy eating in nursery schoolchildren: A quasi-experimental intervention study - Korwanich K. (2014)
Objective: To evaluate the effects of implementing a healthy eating policy on nursery schoolchildren's dietary practices in nurseries in Phrae Province, Thailand. Design: Quasi-experimental action research was used to compare the effects of school healthy eating policy on the diets of nursery schoolchildren in eight intervention and eight matched control schools. Setting: Sample was 219 nursery schoolchildren aged four to five years attending 16 schools in Muang district, Phrae Province, Thailand. Method: School healthy eating policy was implemented in intervention schools with the active participation of the school board members, teachers and parents. Snack intakes of 219 nursery schoolchildren in intervention and control groups were assessed through direct observation by trained observers and a three-day dietary record. Dietary data on snack consumption was collected at baseline and nine months after implementing a healthy eating policy. Results: After nine months, the consumption of every snack item, except non-sugar milk, decreased significantly in intervention schools compared to the baseline (p <.05), but not in control schools. In intervention schools the mean frequency of intakes per day decreased for cariogenic snacks, fresh fruits, Thai desserts, crispy snacks and sugary drinks. On the other hand, in control schools, the mean frequency of consumption per day of cariogenic snacks, non-sugar milk and crispy snacks increased significantly (p <.05). In the control schools, no difference was found between baseline and after nine months in consumption of fresh fruit, Thai desserts and sugary drinks consumption. Conclusion: Healthy eating policy for nursery schoolchildren was effective in reducing snack consumption in intervention schools. Copyright © SAGE 2007.